DEVISING AN EXAMINATION SCHEME OF HEARING IN CHILDREN RECEIVED CHEMOTHERAPY WITH PLATINUM - G.S Tufatulin; Yu.S. Garbaruk (Педиатрическая фармакология)
Over the past few decades significant advances in the treatment of children with oncological diseases have been obtained. In this regard an issue of the life quality of patients after treatment, the problem of diagnosis and therapy of long-term complications of chemotherapy is particularly actual. Purpose of the work — to develop the audiologic examination scheme of children treated with platinum drugs (carboplatin, cysplatin). We examined 46 children aged from 3 months to 18 years. As an audiological methods we used different classes of otoacoustic emissions, tympanometry, tonal threshold audiometry. In 15,2% of children with normal hearing thresholds at speech frequencies we revealed a high frequency hearing loss, and in 8,7% — a sensoneural hearing loss and in 6,5% — conductive hearing loss. During the dynamic examination the progressed deafness took place in 7 (12) children. On the base of the obtained results we determined the most optimal scheme of audiologic examination. Key words: ototoxicity, platinum drugs, otoacoustic emission hearing screening. (Pediatric pharmacology. — 2011; 8 (6): 88–92).